The Chicago Review Press NCLEX-PN practice test and review - Waide, Linda; Roland, Berta (Chicago Review Press, 2004)
Fully revised to conform to the 2003 NCLEX Test Plan, this study guide and test includes "hot spot," fill-in-the-blank, and check-the-box questions to reflect the new test format with 10 written practice tests covering all the body systems, plus two additional practice tests on mental health and miscellaneous topics. Altogether, more than 500 practice test items are provided. Each practice test includes a system overview and complete rationales and explanations for both correct and incorrect answers. Also offered are explanations of how the computerised licensure exam is administered.